Designed for inclusion: André Delbecq's approach in multi-faith environments. Issue 1 (1st January 2020) - Williams, Peter; Allen, Stuart
ABSTRACT: In this article and the accompanying video of André Delbecq, readers gain a glimpse of his respectful, hospitable posture towards others in the multi-faith classroom and workplace. The video provides the viewer with evidence of André's wisdom and insight into the importance of listening and being hospitable to those of other faiths (or non-faiths), including his approach to this topic in higher education. The article includes a review of his writings throughout his career demonstrating that his respect for all members of a diverse community since his earliest work.